The ‘problem’ of undesigned relationality: Ethnographic fieldwork, dual roles and research ethics - Bell, Kirsten (Ethnography, 2019)
Perhaps the most unique feature of ethnographic fieldwork is the distinctive form of relationality it entails, where the ethnographer’s identity as a researcher is not fixed in the way typical of most other forms of research. In this paper, I explore how this ‘undesigned relationality’ is understood, both in procedural ethics frameworks and by the different disciplines that have come to claim a stake in the ‘method’ itself. Demonstrating that the ethical issues it entails are primarily conceptualized via the lens of the ‘dual role’, I use this as a means of exploring the ideal relationship between researcher and subject that procedural ethics frameworks are premised upon. I go on to explore the epistemological differences in ways that ethnographers themselves understand and respond to the multiple forms of relationality that characterize fieldwork and the challenge this poses to the possibility of a pan-disciplinary consensus on ethnographic research ethics.